Survival of Esophageal Cancer in China: A Pooled Analysis on Hospital-Based Studies From 2000 to 2018 - Hou, Haifeng; Meng, Zixiu; Zhao, Xuan; Ding, Guoyong; Sun, Ming; Wang, Wei; Wang, Youxin (Frontiers in Oncology, 2019)
Background: Esophageal cancer (EC) causes more than 400 thousand deaths per year, and half of them occur in China. There are discrepancies on the survival of the EC between population-based surveillance studies and hospital-based studies. Objectives: We aimed to synthesize the survival data from hospital-based EC studies in Chinese population from 2000 to 2018, and to compare the survival rates between EC patients with different clinical classifications. Methods: The protocol of this systematic review was registered in PROSPERO (CRD-42019121559). We searched Embase, PubMed, CNKI and Wanfang databases for studies published between January 1, 2000 and December 31, 2018. We calculated the pooled survival rates and 95% confidence intervals (CIs) by Stata software (V14.0). Results: Our literature search identified 933 studies, of which 331 studies with 79,777 EC patients met inclusion criteria were included in meta-analyses. The pooled survival rates were 74.1% (95% CI: 72.6-75.7%) for one-year survival, 49.0% (95% CI: 44.2-53.8%) for two-year survival, 46.0% (95% CI: 42.6-49.5%) for three-year survival, and 40.1% (95% CI: 33.7-46.4%) for five-year survival, respectively. An increased tendency toward EC survival was verified from 2000 to 2018. In addition, discrepancies were observed between EC patients with different clinical classifications (e.g. stages, histologic types, and cancer sites). Conclusions: Our findings showed a higher survival rate in hospital-based studies than population-based surveillance studies. Although this hospital-based study is subject to potential representability and publication bias, it oﬀers an insight into the prognosis of patients with EC in China.